SINDIRAN DAN MAKIAN DALAM UNGGAHAN DI FACEBOOK PASCADEBAT I PILPRES 2019 (Insinuation and Cursing Uploaded on Facebook during the First Post-Debate at Presidential Election 2019) - R Saleh; Marnetti Marnetti (SAWERIGADING, 2020)
The first debate of the presidential election attracted a lot of attention to internet users and uploaded their comments on social media, one of which is on Facebook. The status and comments uploaded on Facebook are in the form of insinuation, ridicule, and swearing that may violate the law, in particular, defamation. Based on the phenomenon, the study aims 1) to describe the lexical meanings of words used by Facebook users, 2) to describe the grammatical meanings (phrases, sentences, and discourses), which are part of the forensic linguistic study. The research data has collected by using the note-taking method. Data analysis techniques refer to lexical and grammatical semantic theories to obtain the actual meaning of words, phrases, sentences, and discourses from the owners of Facebook. The results of the research indicate that 1) there are 12 accounts of 7 data (screenshot) at Facebook containing insinuation, cursing, and swearing to candidates of the president and vice president 2019 as well as among Facebook users, and 2) words, phrases, sentences, and discourses used by Facebook users, are categorized as defamation and can be used by the authority as the basis for making decisions and giving legal sanctions to perpetrators. Through this research found that there are considerably uploading on Facebook in the form of insinuation, cursing, and swearing conducted by netizens.AbstrakDebat Pilpres tahap I banyak menyisakan perhatian warganet dan mengunggah komentarnya di media sosial, salah satunya facebook. Status dan komentar yang diunggah di facebook banyak berupa sindiran, cemoohan, dan umpatan yang mungkin berpeluang melanggar hukum, terutama defamasi. Berdasarkan masalah tersebut, penelitian ini bertujuan untuk 1) mendeskripsikan makna leksikal kata yang digunakan oleh pengguna facebook, 2) mendeskripsikan makna gramatikal (frasa, kalimat, dan wacana) yang merupakan bagian dari kajian linguistik forensik. Data penelitian ini dikumpulkan dengan metode simak catat. Teknik analisis data mengacu pada teori semantik leksikal dan gramatikal untuk memeroleh makna sebenarnya dari kata, frasa, kalimat, dan wacana pemilik akun. Hasil penelitian ini menunjukkan bahwa 1) sebanyak 12 akun dari 7 data (hasil tangkap layar) di facebook, berdasarkan makna katanya mengandung sindiran, makian, dan umpatan terhadap pasangan calon presiden dan wakil presiden 2019 serta antarsesama pengguna Facebook, dan 2) kata, frasa, kalimat, dan wacana yang digunakan oleh pemilik akun di facebook dikategorikan sebagai defamasi sehingga dapat dimanfaatkan oleh pihak berwenang sebagai salah satu dasar pengambilan putusan dan pemberian sanksi hukum bagi pelakunya. Melalui penelitian ini ditemukan banyak unggahan di facebook yang berupa sidiran, makian, dan umpatan yang dilakukan oleh warganet.